Should the Asian NICs peg to the yen? - Helmut Reisen; Axel Trotsenburg (Intereconomics, 1988)
Recently, the calls for closer monetary co-operation between the Asian NICs and Japan have been becoming louder. The following article discusses the pros and cons of pegging to the yen and compares them with those of a basket peg.
Keywords: 330; Exchange Rate Policy